Analisis Implementasi Kurikulum Merdeka Berdasarkan Instrumen Program Management Office - Noviyanti, Ade Irma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the implementation of the Independent Curriculum using the PMO (Program Management Office) instrument at TK Kemala Bhayangkari 31 Tanggul. The research method used is narrative qualitative with a case study approach. The sample taken was one school using a purposive sampling technique, namely Kemala Bhayangkari Kindergarten 31 Tanggul, Jember Regency, where the school is one of the Mobilizing Schools that implements the Independent Curriculum. Data were obtained using the PMO instrument with a rating scale which was then analyzed using descriptive qualitative techniques. The results showed that the implementation of the Independent Curriculum at Kindergarten Kemala Bhayangkari 31 Tanggul had gone well as evidenced by the average PMO score at level 4 (four). Keywords: analysis, implementation, independent curriculum, PMO, driving school